FABRICATION AND CHARACTERIZATION OF STARCH BASED BIOPLASTICS WITH PALM OIL ADDITION - Anti Khoerul Fikriyyah; Akbar Hanif Dawam Abdullah; Rahmad Dewantoro (Jurnal Sains Materi Indonesia, 2019)
In this work, starch-based bioplastics in advancing its properties were positively arranged with the addition of palm oil. Starch-based bioplastics were produced by dry blending method and compression technique with mixing starch and glycerol (3:1, w/w) then adding palm oil at various concentration (0%, 2.5%, 5% and 7.5% w/w). Morphology of bioplastics presented that palm oil wrapped bioplastics granules which influenced hydrophobicity properties of bioplastics compared by increasing contact angle of bioplastics from 45.950 (0% of palm oil) to 61.980 (5% of palm oil). This result indicated that the addition of palm oil could develop the properties of bioplastics to hold absorbing water molecules. Moreover, the melting point of bioplastics also affected shifting temperature from 1150 C to be 1000 C that could save the energy needed during heating process. FTIR analysis showed that C=O group at wavenumber 1747 cm-1 was dependable the interaction between starch-glycerol and palm oil. Furthermore, the addition of palm oil would accelerate the biodegradation process. Although the mechanical properties of bioplastics have not increased, the addition of palm oil on bioplastics fabrication is an alternative to improve the characteristic of bioplastics, especially physical, thermal, hydrophobicity and biodegradation properties.